2016
DOI: 10.1111/jspn.12154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in adolescent patients with cancer and adolescent survivors of childhood cancer

Abstract: This research has shown that the studied population scored a sufficient QoL, especially survivors of childhood cancer ones. Moreover, their QoL seemed to be influenced by the stage of treatment, the type of cancer, sex, age, family support, and their level of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
(133 reference statements)
3
9
1
Order By: Relevance
“…Female body dissatisfaction appeared more prominent than male body dissatisfaction. This is consistent with evidence from general and cancer populations (Ata et al, ; Olsson et al, ; Vlachioti et al, ). However, it should be noted that men typically discuss body image concerns less in telephone interviews than other non‐verbal methods, such as self‐report surveys (Milton, Ellis, Davenport, Burns, & Hickie, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Female body dissatisfaction appeared more prominent than male body dissatisfaction. This is consistent with evidence from general and cancer populations (Ata et al, ; Olsson et al, ; Vlachioti et al, ). However, it should be noted that men typically discuss body image concerns less in telephone interviews than other non‐verbal methods, such as self‐report surveys (Milton, Ellis, Davenport, Burns, & Hickie, ).…”
Section: Discussionsupporting
confidence: 91%
“…The extent to which results and clinical implications can be generalised to a broader AYA population with a diverse range of cancers is unclear. Quantitative data have shown AYA body image to worsen as a result of the cancer experience (Bellizzi et al, ), particularly in women (Olsson, Enskär, Steineck, Wilderäng, & Jarfelt, ; Vlachioti, Perdikaris, Megapanou, Sava, & Matziou, ; Zucchetti et al, ). In a Danish study, more than half of AYA patients and survivors reported that cancer had negatively affected their body image, and 45% reported that it negatively affected their feelings of being attractive (Graugaard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is consistent with Elnuweiry, that male was (55.5%) while female was (44.5%) that indicated male with cancer more than female [10]. In addition, the result was agree with Vlachioti et al, which found that 57.1% of the study participants are males, while 42.9% of them are females [11] and supported by Fawzy et al (2013) the result showed that the ratio of males to females was 1.8:1 among study patients [12].…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that (54.1%) of the study participants were diagnosed since more than 2 years, 31 (25.4%) of them were diagnosed since below 1 years, while 25 (20.5%) were diagnosed since 1-2 years, and there is no statistically significant difference in the QOL among children between their different diagnosis years of disease, this result consistent with [11].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation